Carbon dioxide‐in‐water foams stabilized with nanoparticles and surfactant acting in synergy. Issue 9 (16th May 2013) - Worthen, Andrew J.; Bryant, Steven L.; Huh, Chun; Johnston, Keith P.
<x xml:space="preserve">Abstract</x> Synergistic interactions at the interface of nanoparticles (bare colloidal silica) and surfactant (caprylamidopropyl betaine) led to the generation of viscous and stable CO2‐in‐water (C/W) foams with fine texture at 19.4 MPa and 50°C. Interestingly, neither species generated C/W foams alone. The surfactant became cationic in the presence of CO2 and adsorbed on the hydrophilic silica nanoparticle surfaces resulting in an increase in the carbon dioxide/water/nanoparticle contact angle. The surfactant also adsorbed at the CO2–water interface, reducing interfacial tension to allow formation of finer bubbles. The foams were generated in a beadpack and characterized by apparent viscosity measurements both in the beadpack and in a capillary tube viscometer. In addition, the macroscopic foam stability was observed visually. The foam texture and viscosity were tunable by controlling the aqueous phase composition. Foam stability is discussed in terms of lamella drainage, disjoining pressure, interfacial viscosity, and hole formation. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3490–3501, 2013